Creating an Inclusive Society… How Close are We in Relation to Autism Spectrum Disorder? A General Population Survey. Issue 4 (25th March 2015) - Dillenburger, Karola; McKerr, Lyn; Jordan, Julie Ann; Devine, Paula; Keenan, Mickey
<x xml:space="preserve">Abstract</x> Background Children with autism spectrum disorder are increasingly educated in mainstream classrooms in the United Kingdom (Wilkinson & Twist, Autism and Educational Assessment: UK Policy and Practice. NFER, Slough, 2010), and some employers are now specifically seeking out staff on the autism spectrum. Does that mean that we are living in an 'inclusive society' [United Nations Department of Economic and Social Affairs (UNDESA), Creating an Inclusive Society: Practical Strategies to Promote Social Integration 2008], in the sense that inequalities are reduced and full economic, social and cultural participation is advanced for individuals with autism? Methods A general population survey was conducted to assess how close we, as a society, are to an inclusive society for individuals with autism in Northern Ireland. Public attitudes were examined to (i) visibility and social interaction, (ii) aetiology, needs and interventions, and (iii) rights and resources. Results A stratified, representative sample of 1204 adults took part in the survey; of these, 989 were aware of autism and their attitudes and behavioural projections reflected a mix of acceptance and denunciation. The level of confusion with regard to interventions reflected the general uncertainty within UK policy regarding meeting the needs of individuals on the autism spectrum (International Journal of Disability, Development and Education 61, 134, 2014a). Conclusion Therefore, it seems that inclusion is working to an extent, but more clarity is needed with regard to adequate education, intervention and support for individuals with autism.